Kosovelovi Integrali in filozofska misel F. Nietzscheja - Polanc-Podpečan, Gizela (Jezik in slovstvo, 2002)
With its mental disposition Srečko Kosovel's collection of poems Integrals (Integrali) is linked to the philosophical thought of Friedrich Nietzsche. Nietzsche's call for the Übermensch, a superhuman being who will shape the new image of Europe, is reflected also in Kosovel´s integral poetry. The integral, which in mathematics means something qualitatively new, a new function we arrive at by creating an endless string of infinitely small variables, is given by Kosovel precisely these dimensions: a series of positive changes may bring about a new ethic image of Europe. The new image of Europe is recognizable in Kosovel's poetry also changes of old values, discussed by Nietzsche in his works Beyond Good and Evil, The Birth of Tragedy, and Thus spoke Zaratustra. Salvation of Europe is put into the hands of the active nihilist, the Űbermensch.
Keywords: Kosovel, Srečko, 1904-1926; Nietzsche, Friedrich, 1844-1900; Slovene literature; slovenska književnost; slovenska poezija; Kosovel, Srečko: Integrali; nemška filozofija; constructivism; konstruktivizem; vplivi